Factors influencing customer’s intention to continuously use cashless transaction mode among Universiti Malaysia Kelantan (UMK) students - Nurashikin Mohd Abdul Latif; Wan Ahmad Syahmi Hilman Wan Ahmad Khalil; Fatimah Azzahra Zainodin; Nur Amierah Mohd Sakri (2023)
This study examines factors influencing customers’ intention to continuously use cashless transaction mode among Universiti Malaysia Kelantan (UMK) students using a well-established model Theory of technology acceptance (TAM) and Unified Theory of Adoption and Use of Technology (UTAUT). A total of 353 completed and usable questionnaires were collected from students UMK to test the hypotheses. The results also find that perceived ease of use, perceived trust, and facilitating condition are positively related to the intention to continuously use cashless payments. Mobile banking, instant payments, and digital commerce are some of the trends affecting the payments market. This study evidenced the effect of the intention to continuously use cashless payment on the correlations between the predictors and the adoption of online transactions. The study outcomes serve to make the payment process easier and more convenient for users. The e-commerce sector is witnessing a spike in demand as consumers order essential items such as food and clothes through e-commerce websites, where most consumers among students prefer the digital mode of payment. It is concluded that the evolution of digital payment systems will be convenient, safe, and can use time-limitless transactions. Privacy, convenience, security, and decentralization will mean wider inclusion for all global citizens regardless of age. Moreover, young people now use advanced technology in their daily life. Ultimately, factors perceived ease of use, trust and facilitating condition encourage higher online banking adoption rates in developing countries.